Il trattamento protesico delle fratture omerali prossimali - Stoppani, C.; Fossati, C.; Randelli, P.S. (Lo Scalpello - Journal, 2019)
SHOULDER ARTHROPLASTY IN THE TREATMENT OF PROXIMAL HUMERAL FRACTURESShoulder arthroplasty is currently the gold standard in the treatment of complex displaced proximal humeralfractures with high risk of avascular necrosis. Hemiarthroplasty was extensively used in the past; however, it presentsa wide variability of clinical outcomes. Recently, reverse total shoulder arthroplasty showed good results in elderlypatients with severe osteoporosis and rotator cuff tears.